Javier Marías and Antonio Muñoz Molina: between two languages - Amador Moreno, Carolina P. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The reader that Spanish novelists Javier Marías and Antonio Muñoz Molina have in mind in Todas las Almas, Corazón tan blanco and Carlota Fainberg is not only an educated reader , but also a reader who is presumed to be pro-ficient in English, and who will, therefore, be able to comprehend the numerous examples of code-switching, the “philological dissections” and cultural references to the English-speaking world that appear in their respective novels. This paper shows how these two authors create fictional images of linguistic interference and translation in order to add credibility to both their characters and narrators. It also addresses the question of whether or not, while still writing from an une quivocally Spanish perspective, they manage to successfully integrate (both in aesthetic terms and in terms of mimetic accuracy) elements pertaining to the English-speaking world into their novels, endowing them with an intercultural dimension.